Use of womac (western ontario and mcmaster university osteoarthritis index) as an indicator for total knee replacement in primary osteoarthritis of knee - Narhari, Prashant (2013)
Total knee replacement (TKR) is an excellent procedure for patients above age of fifty with knee osteoarthritis (OA) presenting with moderate to severe pain and significant disability in daily function not responding to conservative treatment. However there is no simple yet practical tool to guide in indicating patients for the procedure. The WOMAC score has been extensively used both in clinical and experimental setting in assessing patients with knee osteoarthritis. It is reliable. responsive and extensively validated. However its use to decide on need for TKR in patients with primary knee OA is limited. Seventy four patients were scored using the WOMAC scale and were separately assessed by either one of the arthroplasty surgeon for indication to undergo TKR. There were 55 females and 19 males with mean age of 62.47 years ranging between 50 to 86 years old. Majority of the patients were Malays (88%) followed by Chinese (8%), Siamese (3%) and Indian (1%). Kappa statistics noted near perfect agreement (kappa value: 0.833) between the two assessing arthroplasty surgeons. There was a significant difference in the total WOMAC score as well as the three components of the WOMAC score between those patients who need TKR and those who do not. For those who need TKR the mean pain, stiffness and physical function score were 8.29 with SD of 4.17, 4.12 with SD of 1.81 and 30.21 with SD of 9.33 respectively. The mean score for those who do not need TKR was 2.33 with SD of 2.23, 1.93with SD of 1.59 and 9.63 with SD of 6.55 for pain, stiffness and physical function scores respectively. The mean total WOMAC score for those who need TKR was 42.62 with SD of 12.70 and the mean total WOMAC score for those who do not need TKR was 13.88 with SD of 8.27 (p <0.001). The receiver operating characteristic (ROC) curve showed at the cutoff point of 30 on the total WOMAC scale, the specificity and sensitivity for need of TKR was 91.18% and 95.00% respectively. The positive predictive value was 93.24%. The WOMAC score is an excellent tool that can be used to indicate TKR in patients with primary knee OA. The study recommends that all patients with a score of 30 and above should be referred to an arthroplasty surgeon for proper assessment on need of TKR.